2022
DOI: 10.1109/jstars.2022.3197794
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Reflected GPS Signals With Multispectral Imagery to Estimate Soil Moisture at Subfield Scale From Small UAS Platforms

Abstract: This study proposes a low-cost and "proof-of-1 concept" methodology to obtain high spatial resolution soil 2 moisture (SM) via processing reflected Global Positioning System 3 (GPS) and a multispectral camera data acquired by small 4 Unmanned Aircraft System (UAS) platforms. An SM estimation 5 model is developed using a random forest (RF) machine-learning 6 (ML) algorithm by combining features obtained from reflected 7 GPS signals (collected by smartphones and commercial off the 8 shelf receivers) in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In the field of remote sensing, GNSS-R technology has received increasing attention, and many scientists are continuously researching it. GNSS-R technology has been widely used to monitor sea level height [4][5][6], snow depth [7][8][9], soil moisture [10][11][12], and sea ice detection [13,14], etc. In the field of snow depth retrieval technology, Larson et al [15] used global positioning system (GPS) receivers and traditional methods to monitor heavy snowfall, respectively, and the experimental results showed that the snow depth could be effectively monitored using GPS receivers, and the monitoring results were very similar to the classical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of remote sensing, GNSS-R technology has received increasing attention, and many scientists are continuously researching it. GNSS-R technology has been widely used to monitor sea level height [4][5][6], snow depth [7][8][9], soil moisture [10][11][12], and sea ice detection [13,14], etc. In the field of snow depth retrieval technology, Larson et al [15] used global positioning system (GPS) receivers and traditional methods to monitor heavy snowfall, respectively, and the experimental results showed that the snow depth could be effectively monitored using GPS receivers, and the monitoring results were very similar to the classical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its outstanding height measurement performance, GNSS-IR technology is often used to detect snow depth (Larson et al 2009, Tabibi et al 2017, Zheng et al 2022a, sea level height (Jin et al 2011, Larson et al 2013, Löfgren et al 2014, Wang et al 2019, Zheng et al 2021, soil moisture (Chew et al 2014, Senyurek et al 2022, and sea ice thickness (Strandberg et al 2017 and so on. However, only a few scholars have studied the height measurement performance of low-cost equipment, let alone the impact of different station heights on measurement performance.…”
Section: Introductionmentioning
confidence: 99%